ANALISIS BIAYA OPERASIONAL DAN PENDAPATAN PADA CV. HM HAJIRA GALON DI KECAMATAN WAWO KABUPATEN KOLAKA UTARA - Afta, Afta; Sabarudin, Sabarudin; Bustang, Bustang (Komunitas Manajemen Kompetitif, 2025)
This research aims to evaluate the structure of operational costs and revenue generated by CV. HM Hajira Galon, located in Wawo District. The findings indicate that one of the company's key strategies is maintaining the quality of raw materials to ensure the consistent quality of its bottled water products. This commitment to product quality has a positive impact on customer satisfaction, which in turn fosters customer loyalty toward Hajira Refillable Drinking Water Depot. The pricing strategy adopted by the company follows the cost-plus pricing method, resulting in a selling price that is relatively higher than the company's previous pricing calculations. In terms of operational expenditures, the total monthly production cost amounts to IDR 18,838,000, while administrative expenses are recorded at IDR 2,600,000 per month. The total monthly revenue reaches IDR 30,000,000. After deducting total operational costs of IDR 21,438,000, the business earns a net profit of IDR 8,562,000 per month